Yam propagation using 'aeroponics' technology (2014)
Aims: To study yam propagation and seed yam tuber production in aeroponics system. Study Design: The experiment was conducted in a randomized complete block design and treatments were replicated three times. Place of Study: This experiment was carried out at the International Institute of Tropical Agriculture Headquarters at Ibadan in Nigeria. Methodology: The experiment tested fresh vine cuttings of five yam genotypes of two species in an aeroponics system. Three genotypes of Dioscorea rotundata (TDr 89/02475, TDr 89/02665 and TDr 95/18544) and two yam genotypes of D. alata (TDa 98/01176 and TDa 291) were evaluated. Results: Vines of both D. rotundata and D. alata rooted within 2 weeks in aeroponics system. The rooting of vine cuttings varied significantly among genotypes with a maximum of 98% for TDa 98/01176 and a minimum of 68% for TDr 89/02665. Mini-tubers harvested after 4 months of growth in aeroponics weighed between 0.2 and 2.7g. A second harvest 6 months later gave mini-tubers of up to 110g. The analysis of variance showed significant difference (P<0.05) among genotypes for rooting at 2 weeks after vine planting, number of plant surviving at 90 days after planting and percentage of plants with bulbils. The best genotypes were TDr 95/18544 and TDr 89/02665 for survival at 90 days after vine planting and percentage of plant producing bulbils in the aeroponics system respectively. Conclusion: This study revealed that yam genotypes performed differently in aeroponics system for vine rooting and production of mini-tubers and bulbils.